FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DIARE PADA ANAK UMUR 0 – 24 BULAN YANG DIRAWAT DI RSI “IBNU SINA” YARSI SUMBAR PAYAKUMBUH TAHUN 2017 - Putri Aulia Arza (Jurnal Gizi, 2018)
Diarrhea is the second leading cause of death in children under five years. Diarrhea disease in children is the most cases of disease that exists in the Islamic Hospital "Ibnu Sina" YARSI in Payakumbuh, West Sumatra. Diarrhea cases recorded as much as 32.25% are children under the age of two years.               This study aims to determine the factors associated with the incidence of diarrhea in children aged 0-24 months. This study was conducted on 16 March - 16 May 2017 using a quantitative approach to the cross-sectional design. The population is the mother who has children aged 0 - 24 months who hospitalized at Islamic hospital "Ibnu Sina" Yarsi in Payakumbuh, West Sumatra. Samples taken as many as 60 peoples with accidental sampling technique. Univariate analysis performed to present the frequency distribution table. Bivariate analysis using  chi-square statistical test.               The result of the univariate analysis showed that 41.7% of children who were treated 0-24 months old had diarrhea, 55.0% of respondents had good knowledge of diarrhea, 53.5% of respondents had positive attitude related to diarrhea, 50.0% Both about breastfeeding and 55.0% have a bad attitude related to the provision of MP-ASI. The result of Bivariate is no relationship of knowledge with the occurrence of diarrhea (p-value = 0,148), there is no relationship of attitude with diarrhea (p-value = 0,484) and there is a relationship of breastfeeding behavior (p-value = 0,004) and the behavior of  MP-ASI with diarrhea occurrence (P-value = 0,000).               It is expected that mothers with children under five to pay attention to the behavior in breastfeeding and giving of breast milk is also about children's health in general so that children avoid disease.